Risk of breast cancer and prediagnostic urinary excretion of bisphenol A, triclosan and parabens: The Multiethnic Cohort Study. Issue 7 (3rd June 2021) - Wu, Anna H.; Franke, Adrian A.; Wilkens, Lynne R.; Tseng, Chiuchen; Conroy, Shannon M.; Li, Yuqing; Sangaramoorthy, Meera; Polfus, Linda M.; DeRouen, Mindy C.; Caberto, Christian; Haiman, Christopher; Stram, Daniel O.; et al.
Abstract: Exposure to bisphenol A (BPA), triclosan and parabens is widespread but their impact on breast cancer risk remains unclear. This nested case‐control study investigated endocrine‐disrupting chemicals (EDCs) and breast cancer risk within the Multiethnic Cohort (MEC). We measured prediagnostic urinary BPA, triclosan and parabens in 1032 postmenopausal women with breast cancer (48 African American, 77 Latino, 155 Native Hawaiian, 478 Japanese American and 274 White) and 1030 individually matched controls, using a sensitive and validated liquid chromatography mass spectrometry assay. Conditional logistic regression was used to examine risk with these EDCs with adjustment for creatinine and potential confounders. In all women, breast cancer risk was not associated with BPA ( P trend = 0.53) and was inversely associated with triclosan (ORT3 vs T1 = 0.83, 95% CI: 0.66‐1.04, P trend = 0.045) and total parabens (ORT3 vs T1 = 0.77, 95% CI: 0.62‐0.97, P trend = 0.03). While risk of hormone receptor positive (HR+) cancer was 20% to 23% lower among women in the upper two tertiles of paraben exposure ( P trend = 0.02), risk of HR negative (HR−) was reduced 27% but only among those in the upper tertile of exposure. Although risk associations did not differ significantly by ethnicity or by body mass index (BMI), the inverse association with triclosan was observed mainly among overweight/obese women (ORT3 vs T1 = 0.76, 95% CI: 0.56‐1.02, P trend = 0.02). In summary, breast cancer risk in a multiethnic population was unrelated to BPA and was weakly inversely associated with triclosan and paraben exposures. Studies with multiple urine samples collected before breast cancer diagnosis are needed to further investigate these EDCs and breast cancer risk.